2023
DOI: 10.1021/acs.chemmater.2c03337
|View full text |Cite
|
Sign up to set email alerts
|

Facile Solid-State Synthesis of Supported PtNi and PtCo Bimetallic Nanoparticles for the Oxygen Reduction Reaction

Abstract: Proton-exchange membrane fuel cells (PEMFCs) represent an essential technology for the future decarbonization of the transportation sector. A major component of PEMFCs is the catalyst, often Pt-based alloys supported on carbon black, which are sufficiently active and stable upon long-term operation under the harsh reaction conditions implied by PEMFCs. However, the catalyst synthesis is typically laborious and challenging to upscale, employing organic solvents, surfactants, or uneconomical metal deposition rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Due to their concave and high refractive index surfaces as well as synergistic effects between Pt and Co atoms, the PtCo CNCs exhibit significantly enhanced methanol oxidation activity and excellent electrocatalytic stability. In general, the current methods for synthesizing PtCo catalysts mainly include liquid-phase reduction, solid-phase reduction, electrochemical synthesis, and impregnation reduction. The liquid-phase reduction method often requires the selection of a suitable surfactant for capping, yet the surfactant is generally difficult to remove. Electrochemical methods can prepare homogeneous films but are not very controllable.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their concave and high refractive index surfaces as well as synergistic effects between Pt and Co atoms, the PtCo CNCs exhibit significantly enhanced methanol oxidation activity and excellent electrocatalytic stability. In general, the current methods for synthesizing PtCo catalysts mainly include liquid-phase reduction, solid-phase reduction, electrochemical synthesis, and impregnation reduction. The liquid-phase reduction method often requires the selection of a suitable surfactant for capping, yet the surfactant is generally difficult to remove. Electrochemical methods can prepare homogeneous films but are not very controllable.…”
Section: Introductionmentioning
confidence: 99%
“…When this method is extended to the synthesis of bimetallic supported catalysts, an additional issue caused by the metal-metal interaction comes into the play, making a systematic approach difficult but highly desirable. So far, the number of research papers on supported bimetallic (thermo) catalysts obtained by ball milling is still quite limited [12][13][14][15][16][17][18][19][20][21][22]. However, some important elements have been highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous deposition of two metals can already be successfully obtained in short milling times and with relatively mild energy [13,19,21], but it strongly depends on the choice of the precursors and, possibly, on the support. Metal co-deposition is relatively easy with the appropriate conditions, but the formation of an alloy usually requires subsequent thermal treatments [13,20,21,23]. Interestingly, it has been found that energy-intensive thermal steps can be overcome by longer milling times [11,14,24], even if this can lead to the contamination of the catalyst by the milling media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation